O trágico revisitado na pós- modernidade: A construção da ação dramática em closer, de Patrick Marber - Vasconcelos, Leonardo Monteiro de (2015)
Closer, the most famous Patrick Marber’s play, was studied by theater critic in the 1990s, and it was acclaimed to be a representative work of the human relations in contemporary world by portraing the transience of love relations. The play depicts the relationship of four characters who change partners between each other , apparently without cause and / or reason. Closer is a postmodern play par excellence not only due to language and theme, but also its connection to the so-called In-Yer-Face Theatre, which started back in the mid 90s in England, whose main goal was to report political, economical and social problems in that country. In this dissertation, we intend to study the construction of the dramatic action in Closer. Although, the play is set in a contemporary period, it presents elements which refers back to the arestotelian Aesthetic. So, we’ll study the elements of a tragic action inserted in a postmodern context. Besides studying the play as a tragic format, we are going to study the play according to the theory of the tragic in postmodern societies coined by Michel Maffesoli. Due to these reasons, we intend to contribute to the literary studies with a research which disscusses tradition and postmodernity.